The road to terror : Stalin and the self-destruction of the Bolsheviks, 1932-1939 - Getty, J. Arch (John Arch), 1950-; Naumov, Oleg V. (New Haven, Conn : Yale University Press, 1999)
"The vast and complex tragedy of Stalin's purges, culminating in the Great Terror, made victims of millions of Russians between 1932 and 1939. This book assembles and translates into English for the first time an astonishing array of formerly top secret Soviet documents from that period. Exposing to daylight the hidden inner workings of the Communist Party and the dark inhumanity of the purge process, these documents immeasurably deepen our understanding of an agonizing episode of Soviet history."--Jacket
Introduction: Party documents and Bolshevik mentality -- Part I. Closing ranks. The new situation, 1930-32 -- Party discipline in 1932 -- Repression and legality -- Growing tension in 1935 -- Screening cadres -- The fork in the road -- Pat II. The terror. The face of the enemy, 1936 -- The tide turns -- The sky darkens -- Party discipline and the fall of Bukharin -- The storm of 1937: the party commits suicide -- Ending the terror, 1938 -- Two Bolsheviks.
Includes bibliographical references and indexes.
Print version record.
JSTOR
Keywords: Kommunisticheskai͡a partii͡a Sovetskogo Soi͡uza -- Purges -- Sources; Stalin, Joseph, -- 1878-1953 -- Sources; Stalin, Iosif, -- 1879-1953 -- Sources; Kommunističeskaja partija Sovetskogo Sojuza -- Purges -- Sources; Stalin, Joseph, -- 1878-1953; Kommunisticheskai͡a partii͡a Sovetskogo Soi͡uza; Political purges -- Soviet Union -- History -- Sources; Soviet Union -- Politics and government -- 1917-1936 -- Sources; Soviet Union -- Politics and government -- 1936-1953 -- Sources; Terrorism -- Soviet Union -- Sources; Purges politiques -- URSS -- Histoire -- Sources; Terrorisme -- URSS -- Sources; URSS -- Politique et gouvernement -- 1917-1936 -- Sources; URSS -- Politique et gouvernement -- 1936-1953 -- Sources; HISTORY; Political purges; Politics and government; Terrorism; Soviet Union; Bolsjewisme; Terrorisme; 1917-1953; History; Sources; Bronnen (vorm)